2012
DOI: 10.1080/13674676.2011.574272
|View full text |Cite
|
Sign up to set email alerts
|

Religious doubt, financial strain, and depressive symptoms among older Mexican Americans

Abstract: Purpose A number of studies suggest that positive aspects of religion (e.g., social support from fellow church members) help older people cope more effectively with stress. However, researchers have known for some time that there are negative as well as positive facets of religion. This suggests that instead of enhancing coping efforts, religion may also exacerbate the effects of stress. The purpose of this study was to see if one negative aspect of religion (i.e., religious doubt) exacerbates the effects of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
1
12
3
Order By: Relevance
“…This finding is consistent with a growing body of research on religion and health which suggests that the positive benefits of religious participation are not enjoyed by everyone (Ellison and Lee 2010;Ellison et al 2009;Krause 2011c). Although many non-Catholics stand to gain from their active involvement in religious organizations, the CIA World Factbook lists more than a dozen countries with Catholic populations of 90 % or more, including most of Latin America.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding is consistent with a growing body of research on religion and health which suggests that the positive benefits of religious participation are not enjoyed by everyone (Ellison and Lee 2010;Ellison et al 2009;Krause 2011c). Although many non-Catholics stand to gain from their active involvement in religious organizations, the CIA World Factbook lists more than a dozen countries with Catholic populations of 90 % or more, including most of Latin America.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, 80 % of studies examining the relationship between religion and life satisfaction find a positive association (Koenig and Larson 2001). In fact, even Krause (2011c) and Mochon et al (2011) conclude that the effects of religion are largely positive for those with stronger religious beliefs.…”
Section: Religion and Well-beingmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research conducted primarily in Western countries has found that degree of religiosity is directly related to suicidality, with greater religiosity predicting fewer suicidal thoughts, attempts, and completed suicide [12, 13, 29]. Several reasons could explain the difference between our findings and the vast majority of other studies in this area.…”
Section: Discussioncontrasting
confidence: 83%
“…Religious doubt is another aspect of religion that negatively affects mental health ( Krause, 2012 ). Older Latinos who report more religious doubt have higher levels of depressed affect ( Krause & Hayward, 2012 ) and cognition ( Krause, 2012 ) and greater somatic depressive symptoms ( Krause & Hayward, 2012 ). Among older blacks, religious doubt is also associated with more depressive symptoms ( Willis et al, 2019 ).…”
Section: Negative Side Of Religionmentioning
confidence: 99%